2013
DOI: 10.1016/j.ejon.2012.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the meaning of fatigue at the end of life: An ethnoscience approach

Abstract: Purpose: Fatigue is a devastating state of body and mind associated with distress at the end of life. We report the results of the third in a series of papers outlining a novel approach we have developed for understanding the meaning of fatigue by exploring how this meaning is shaped by beliefs and values. The aims of the study were to examine the perception and experiences of fatigue held by patients attending a hospice in England; identify the behavioural patterns that distinguish fatigue from tiredness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…These results are consistent with previous research identifying the multiple causes of weakness. 34,35 Hence, professionals should carefully conduct individual assessments on the nature and causes of weakness, thus enabling the effective selection of appropriate care strategies; psychoeducation about the symptom, general nursing strategies, nonpharmacologic and pharmacologic interventions. 36 Weakness was connected to the inability to share feelings with family or friends.…”
Section: Weakness As the Most Crucial Symptommentioning
confidence: 99%
“…These results are consistent with previous research identifying the multiple causes of weakness. 34,35 Hence, professionals should carefully conduct individual assessments on the nature and causes of weakness, thus enabling the effective selection of appropriate care strategies; psychoeducation about the symptom, general nursing strategies, nonpharmacologic and pharmacologic interventions. 36 Weakness was connected to the inability to share feelings with family or friends.…”
Section: Weakness As the Most Crucial Symptommentioning
confidence: 99%
“…A preliminary comparison of the cross-cultural results can be find in the paper by Kirshbaum et al (2010) where preliminary analysis showed that while both "body" and "mind" are central to the nature of fatigue in all four study populations, the dimensions within these two central domains vary thus stimulating discussion surrounding the ways culture shapes the meaning of illness and therefore influence directions toward culturally sensitive interventions. Our results provides further evidences that symptom and illness experience are socially constructed thus suggesting the need to consider that in order to develop effective and tailored interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, valuing patients' subjective illness experience is now more and more recognized as an effective way to foster patients' engagement in their care & cure process thus making interventions more aligned to their unmet needs (Barello et al, 2012). This meaning-making process is strictly connected to the system of values and beliefs of the patients and usually finds its manifestation in their use of language (Kirshbaum et al, 2012). In this research field, a qualitative approach could be particularly suited to capture the nuances of individual experience in a more "ecological" perspective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there remains a clinically significant proportion of the global population for whom a prescription to undertake moderate aerobic would not be advisable nor reasonable; for example, people with mobility, muscle strength and flexibility limitations or specific restriction due to respiratory, cardiac, or advanced cancer conditions. In a recent study on the perceptions of fatigue in advanced cancer (Kirshbaum et al, 2012), this last point was noted first-hand. Participants in the study were all experiencing moderate to advanced levels of fatigue, but were constrained by their advancing limitations; it would have been completely inappropriate to advise increasing their levels of aerobic activity.…”
Section: Introductionmentioning
confidence: 93%